Large subgaleal hematoma caused by valproic acid: a case report : Large subgaleal hematoma caused by valproic acid - da Silva , Aldo José F; Carvalho , Ana Carolina Ruela; Amaral, Fabiana Lopes; da Costa, Auxiliadora Damiane Pereira Vieira (Archives of Pediatric Neurosurgery, 2020)
Introdução: Valproic acid (VPA), used to treat epilepsy, may present hematological abnormalities as complications. One such example is bleeding associated with trauma. We herein report a case about large subgaleal hemorrhage that occurred after a mild head trauma in a child following VPA administration. Case Report: A 12-year-old female child diagnosed with Rett Syndrome had difficulty in controlling epilepsy and was taking 50 mg/kg/day VPA. After suffering from a mild head trauma, a large subgaleal hematoma was evidenced on Computed Tomography(CT) scan of head. Surgical intervention was performed, with drainage of the hematoma, and the patient showed progression. Discussion: The incidence of coagulopathy related to VPA is 4%, and thrombocytopenia is the most common coagulation disorder. Hemorrhagic complications can occur regardless of the plasma levels or duration of treatment. In VPA therapy, the side effects should be considered, particularly hematological abnormalities. In our case, an unusual hemorrhagic complication (subgaleal hematoma) was reported, with good surgical resolution of the pathology.